The Paradigm of Harmonious Progress in Energy - Klevas, Valentinas; Klevienė, Audrone (Cambridge Scholars Publishing, 2020)
This book serves to define the foundation of the idea of harmonious progress in energy. It clarifies the main problem of the current ecological situation, namely the tendency to treat nature as an inexhaustible pool of natural resources and absorber of harsh outcomes of economic activity. Current definitions of progress in this case are equated to technological progress and economic growth, without considering the boundaries of nature's capabilities. This book proposes a revolutionary idea: treating nature and its laws with major respect, as the foundation of all forms of life, defining the bo.